Analysis of fatty acid compositions and concentrations in the kernel of seven main macadamia cultivars in Yunnan - DUAN Minxian; ZHANG Birong; YANG Fan; LI Xuejia; SHI Wenbin; YAN Suyun; TANG Shaoping; ZHAO Jun; ZHOU Xianyan (Guoshu xuebao)
[Objective] Fatty acid is one of the main trait indicators to evaluate the nut quality of macadamia germplasm resources, and also essential nutrients for human health. With the consumers becoming more concerned about healthy foods, large amounts of nutrition-related data are needed to screen excellent nut germplasms. Yunnan is the main producing area of macadamia nuts. This study aims to investigate the differences in fatty acid compositions among seven main varieties in Yunnan and screen macadamia nut varieties rich in specific fatty acids. [Methods] Seven macadamia varieties (A16, 816, Guang 11, HAES344, HAES660, Guire 1 and Changning 1) from the macadamia planting base of the Institute of Tropical and Subtropical Cash Crops, Yunnan Academy of Agricultural Sciences (located in Baoshan city, Yunnan province) were selected as the test materials. Sample collection was carried out by using diagonal method, and 10 plants with the same vigor and without pests and diseases were randomly selected at the maturity stage. Atotal of 60 macadamia nuts were collected from the low, medium, high, inside and outside positions of the canopy, and randomly divided into three groups with 20 fruits in each group. The fresh green peel was husked, the kernel was immediately frozen and ground with liquid nitrogen, and then stored at -80 ℃ for later use. The composition and content of fatty acids per unit fresh weight kernel were detected by liquid chromatography-mass spectrometry (LC-MS) according to 50 fatty acid standards and five stable isotope labeled standards, and one-way analysis of variance (ANOVA), principal component analysis (PCA) and partial least squares discriminant analysis (PLSDA) were used for comprehensive analysis and evaluation. [Results] A total of 41 fatty acids were detected in the kernels of seven macadamia varieties in Yunnan, including 13 saturated fatty acids (SFA), 18 monounsaturated fatty acids (MUFAs) and 10 polyunsaturated fatty acids (PUFAs). In terms of fatty acid content, the SFA contents of the seven varieties ranged from 43 726.20 to 102 759.74 ng·g-1, the MUFA contents from 53 590.74 to 343 559.73 ng·g-1, and the PUFA contents from 8 733.66 to 53 692.72 ng·g-1. Among them, Guang 11 had the highest contents of SFA, MUFA and PUFA, followed by HAES660, and Guire 1 had the lowest values. A further analysis of the contents of various fatty acids in different varieties of macadamia nuts showed that hexadecanoic acid, palmitoleic acid, octadecanoic acid, oleic acid, cis-vaccenic acid and linoleic acid were the main components of 41 fatty acids, among which hexadecanoic acid contents ranged from 20 218.83 to 56 261.30 ng·g-1, palmitoleic acid contents from 10 360.40 to 125 929.28 ng·g-1, octadecanoic acid contents from 13 438.66 to 42 448.98 ng·g-1, oleic acid contents from 18969.29 to 96 976.32 ng·g-1, cis-vaccenic acid contents from 18 741.46 to 95 181.99 ng·g-1, and linoleic acid contents from 7 435.72 to 51 326.26 ng·g-1. The contents of hexadecanoic acid, palmitoleic acid, oleic acid, cis-vaccenic acid and linoleic acid were the highest in Guang 11; the content of octadecanoic acid was the highest in HAES660, and the contents of hexadecanoic acid, palmitoleic acid, oleic acid, cis-vaccenic acid and linoleic acid in HAES660 were second following Guang 11, which were 42 381.88, 46 840.31, 52 791.16, 52 310.95 and 19 096.30 ng·g-1, respectively. The α-linolenic acid contents of Guang 11 and HAES660 was significantly higher than those of other varieties, which were 1 619.06 and 1 777.21 ng·g-1, respectively. Eicosapentaenoic acid (EPA) was highly correlated with human health, and the highest content was found in Guire 1, followed by HAES344, which were 6.26 and 4.77 ng·g-1, respectively. PCA analysis showed that the first principal component PC1 and the second principal component PC2 contained 55.5% and 18.5% of the original information, respectively, and Guang 11 and HAES660 were clearly separated from other varieties. A total of 16 characteristic fatty acids were screened by PLS-DA analysis using VIP>1 as the screening criterion. including decanoic acid, octadecanoic acid, tridecanoic acid, dodecanoic acid, pentadecanoic acid, myristelaidic acid, petroselaidic acid, trans-10-heptadecenoic acid, trans-10-pentadecenoic acid, cis-4,7,10,13,16,19-docosa-hexaenoic acid (DHA), cis-5,8,11,14,17-eicosapentaenoic acid (EPA), linoelaidic acid, cis-13,16-docosadienoic acid, cis-11,14,17-eicosatrienoic acid, arachidonic acid and γ-linolenic acid. Three characteristic fatty acids were screened by VIP>1.5, which were decanoic acid, arachidonic acid and DHA, and the contents of decanoic acid and DHAin cultivar 816 were the highest, which were 54.63 and 120.79 ng·g-1, respectively. Guire 1 had the highest content of arachidonic acid (148.76 ng·g-1). [Conclusion] A total of 41 fatty acids were detected in all seven macadamia varieties in Yunnan, with Guang 11 having the highest content of fatty acids, followed by HAES660. Guang 11 had the highest contents of hexadecanoic acid, palmitoleic acid, oleic acid, cis-vaccenic acid, and linoleic acid; HAES660 exhibited the highest contents of octadecanoic acid and α-linolenic acid; 816 had the highest content of decanoic acid and DHA; and Guire 1 displayed the highest contents of arachidonic acid and EPA.